Heterogeneity of γδ T-cell subsets and their clinical correlation in patients with AML - Jiang, Siyuan; Zheng, Shiyu; Yao, Chao; Ning, Dengchong; Zou, Shaoyun; Zhan, Jiannan; Lan, Tianbi; Yi, Tingzhuang; Jin, Zhenyi; Wu, Xiuli (Frontiers in Immunology, 2025)
Backgroundγδ T cells are integral elements of the immune system and have shown therapeutic potential in the treatment of acute myeloid leukemia (AML). Nevertheless, the influence of distinct functional subsets, including the activating marker NKG2D, the immune exhaustion marker TIGIT, and the regulatory marker Foxp3, on therapeutic outcomes in AML patients remains unknown.MethodsFirst, we analyzed RNA-seq data from 167 patients in The Cancer Genome Atlas (TCGA) database, concentrating on the correlations between NKG2D, TIGIT, and Foxp3 gene expressions and their association with prognosis in AML. We employed flow cytometry to assess the expression of these molecular markers on γδ T cells and the Vδ1/Vδ2 subsets in the peripheral blood of 25 de novo AML (AML-DN) patients, 15 patients in complete remission (CR), and 27 healthy controls (HCs). We also analyzed the relationship between the expression frequencies of NKG2D, TIGIT, and Foxp3 on γδ T cells and their subsets, and their clinical outcomes.ResultsBased on data from TCGA database, we found that a high expression level of NKG2D in combination with a low expression level of TIGIT was significantly associated with longer overall survival (OS) in AML patients. Clinical data revealed that γδ T cells from AML-DN patients exhibited higher expression levels of TIGIT and Foxp3, whereas NKG2D expression was lower compared to that of HCs. Notably, the expression of the NKG2D+TIGIT− Vδ1 subset was significantly reduced in AML-DN patients compared to CR patients. Univariate logistic regression and Cox regression analyses further indicated that a high expression of the NKG2D+TIGIT− Vδ1 subset was associated with better clinical prognosis.ConclusionThis study indicates that NKG2D+TIGIT− Vδ1 T cells are strongly correlated with improved prognosis in AML, and future research should investigate their potential in adoptive immunotherapy to advance more personalized and precise treatment strategies.